Modification variability of the new cultivar of wheat-rye amphidiploid by the ecological, industrial-valuable and molecular-genetic features - Москалець, Т. З.; Гриник, І. В.; Тарасюк, С. І.; Москалець, В. В.; Буняк, Н. М.; Москалець, В. І.; Рибальченко, В. К. (Problems of Environmental Biotechnology, 2015)
Studied ecological, industrial-valuable and molecular-genetic features of the new cultivar of wheat-rye amphidiploid triticale. It is shown that a cultivar Vivate Nosivske derived method of individual selection from the hybrid combination ([Avhusto NE x 312] x K 9844), and highlighted on the adaptability and resistance to a range of adverse abiotic and biotic factors, lodging and germination of the grain in the ear, is ecological stable in performance under Polissia-Forest-steppe and Forest-steppe ecotopes, generates a high yield (more than 9 t/ha) and grain quality (16 % protein) with timely use of science-based elements of farming. It is determined that the starch grains contained in this class is high (19,8 %) amylopectin content compared with amylose as evidenced by the consistency of the dough, its falling number and viscosity, and suitability for the baking of bakery products. This feature cultivar due to the presence in the genotype recessive allele (b) gene Wx-A1, which is responsible for blocking the GBSS – granulebound starch synthase.